THE ROLE OF MORAL AND PSYCHOLOGICAL (PSYCHOLOGICAL) TRAINING IN IMPROVING THE EFFECTIVENESS OF THE RESERVE AND RESERVE OFFICER TRAINING SYSTEM - Ganjiev Shuhratjon Jo‘raevich (Research Parks Publishers, 2023)
This article is a brief overview of the role of moral and psychological (psychological) training in improving the effectiveness of the system of training officers in the Reserve and reserve. This article is designed to closely familiarize Reserve and reserve officers (teachers) in Higher, Secondary special and secondary educational institutions with information on the role of moral and psychological (psychological) training in improving the effectiveness of the Reserve and reserve officer training system.